Evaluation of Maintenance Management Practice in Banking Industry in Lagos State, Nigeria - Faremi, Olajide Julius; Adenuga, Afolami Olumide (International Journal of Sustainable Construction Engineering and Technology, 2012)
The study focused on maintenance management practice in banking industry in Lagos state, Nigeria. It assessed the operational state of bank buildings, the factors affecting maintenance management of bank buildings, the maintenance management strategy used in maintainingbank buildings and the adequacy of funds available for maintenance management of bank buildings within the study area. In achieving these objectives, opinions of maintenanceofficers and users of randomly selected banks were sampled through structured questionnaires. The data collected were analyzed using descriptive and inferential statistics. The analysis revealed the operational state of bank buildings in Lagos State as good, there is no significant difference in the perception of the maintenance staff and users as to the operational state. However, there is significant difference in the operational state of the old and the newgeneration bank buildings as the study reveals that the components and services of the buildings of the new generation banks are in better operational state than those of the old generation bank buildings. Maintenance officers ranked attitude of users and misuse of facilities as the most significant factor affecting maintenance management of bank buildings while users of the buildings ranked lack of discernable maintenance culture in the country asthe most significant factor responsible for poor maintenance management of bank buildings. The perception of the maintenance staff and users of bank buildings as regards factors responsible for poor maintenance management of bank buildings are significantly different. The study recommended proactive measures to keep hypothesized factors under check in other to overcome the prevailing maintenance problems of bank buildings. Top managementare to provide adequate funding for the running of maintenance operations and such funds should be properly monitored to ensure that it is judiciously utilized.